Syrian rue seeds interacted with acacia tree bark in an herbal stew resulted in N, N-dimethyltryptamine poisoning. (3rd October 2019) - Liu, Chuan-Huai; Chu, Wei-Lan; Liao, Shu-Chen; Yang, Chen-Chang; Lin, Chih-Chuan
Abstract: Introduction: Illicit substance use is an increasing problem all over the world, especially in adolescents and young adults. It is a challenge to make a definitive diagnosis of a specific substance in a poisoning case without toxicology laboratory confirmation. We confirmed the presence of N, N-dimethyltryptamine (DMT) by liquid chromatograph tandem mass spectrometer (LC/MS/MS) in biologic samples from two patients who presented with signs and symptoms consistent with sympathomimetic toxicity following the consumption of an herbal stew. Case: Two patients consumed an herbal stew together developed DMT poisoning from the interaction between Syrian rue seeds containing alkaloids with monoamine oxidase inhibitor (MAOI) activity and Acacia tree bark containing DMT. Patients' blood and spot urine was analyzed by LC/MS/MS which revealed the presence of DMT (case 1 urine: 1206 ng/mL, serum: 25 ng/mL; case 2 urine: 478 ng/mL, serum: undetectable) and harmaline (case 1 urine: 1564 ng/mL, serum: 3.3 ng/mL; case 2 urine: 1230 ng/mL, serum: undetectable). Discussion: The diagnosis of DMT poisoning is confirmed by the presence of DMT and harmaline in patients' serum and urine. Case 1 exhibited more severe signs and symptoms (e.g., altered consciousness, rhabdomyolysis, and elevated liver enzyme) than case 2. This may be explained by the presence of psychoactive DMT levels in the blood of case 1 whereas DMT was undetected in the blood of case 2. Conclusions: Consumption of an herbal stew composed of Syrian rue seeds and Acacia tree bark may be equivalent to taking a combination of DMT and MAOI, which may precipitate a sympathomimetic syndrome. Physicians should be aware that unusual clinical presentations may be the result of drug-drug interactions from a mixed herbal preparation.